Perakitan Sistem Monitoring Penggunaan Air PDAM Pada Rumah Tangga Secara Real-Time Berbasis Aplikasi Android - Yanto, Yanto; AlKahfie, Rafly; Fujiyanti, Linda; Josi, Ahmad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Water is an important natural resource for human life, but excessive use can cause a water crisis. This study aims to develop a PDAM water usage monitoring system based on the Internet of Things (IoT) and an Android application to improve the efficiency of water use in households in Bangka Belitung. This system uses a water flow sensor, LCD, ESP8266, and NodeMCU to display data in real-time on a smartphone. With the designed prototype, users can monitor the volume of water consumed and estimated monthly costs via the internet, as well as access data from the Firebase database. The test results show that the waterflow sensor has good accuracy with an average error of 1% to 6%, and the flow rate remains constant at 0.16 Ls per minute even though the water volume varies. This system not only provides convenience in monitoring water consumption but also has the potential to reduce the operational costs of the Regional Drinking Water Company (PDAM). This study provides an innovative solution for better water resource management in the Bangka Belitung Community.